Sins of the Father’s Firm: Exploring Responses to Inherited Ethical Dilemmas in Family Business - Litz, Reginald A.; Turner, Nick (2013)
How do individuals respond when they perceive that their family business has been built upon unethical business conduct? Drawing on an expanded version of Hirschman’s typology of generic responses to declining situations (Exit, Voice and Loyalty: Responses to Decline in Firms, Organizations, and States, Harvard University Press, Cambridge, MA, 1970), which includes responses of Exit, Voice, Loyalty, and Neglect, we offer a model that predicts probability of intended response behavior as a function of normative obligation (i.e., what one perceives ought to be done), managerial discretion (i.e., what one perceives can be done), and successor commitment to the firm. The model is tested on 124 business school students exposed to a scenario depicting an inherited ethical dilemma occurring in a family business from Arthur Miller’s play All My Sons, and shows support for elements of the proposed framework. Most notable is a significant negative relationship between normative firm-directed commitment and the response of Neglect.
Keywords: Dilemma; Inherited; Business; Family